Papers - - Production - Foreign - Petroleum Development in Colombia during 1935 - O. C. Wheeler (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1936)
In past years the exploration of the oil possibilities of Colombia has been confined to parts of three distinct physiographic provinces; namely, the coastal plains area near the Caribbean Sea, the Magdalena Valley and the upper reaches of the Maracaibo Basin near the Venezuelan border. During 1935, little exploratory work and no drilling was carried on on the coast, but there was considerable activity in the other two areas. In the Magdalena Valley, the Tropical Oil Co. continued its producing and development operations on the De Mares Concession. The Socony-Vacuum exercised the option it acquired in 1934 on Sr. Luciano Restrepo's concession adjacent to the Tropical property and north of the Sogamoso River. No wells have been started on the Socony's lands although, according to the terms of the lease, drilling must be started within the next two years. West of the Carare River and adjacent to the Tropical's southwestern boundary, the Sociedad Nacional del Carare denounced the lands formerly held by the Union Colombiana, whose lease automatically lapsed during the year owing to the company's failure to comply with its drilling obligations. In the same area, the concessions held by Callejas et al. and the Société Européene des Pétroles are also understood to have lapsed for the same reason. Holdings of other interests in the Magdalena Valley were inactive during the year. Near the upper part of the Maracaibo Basin, the Gulf, through its subsidiary the Colombian Petroleum Co., continued active exploration and development on its Barco concession. Colombian Petroleum Co.—The following information and that presented in the accompanying tables relating to the activities of the Colombian Petroleum Co. was supplied through the courtesy of Mr. E. S. Bleecker, chief geologist of that company. Four wells were completed during the year on the north Petrolea dome, where an attempt is being made to define the limits of the field. On the south end of the Petrolea anticline, one well, Petrolea No. 3, which might be classed as a wildcat, encountered a heavy flow of salt water immediately below the oil zone and had to be abandoned. A second location has been made 1 miles south of No. 3 and somewhat higher on